Complementary Metaproteomic Approaches to Assess the Bacterioplankton Response toward a Phytoplankton Spring Bloom in the Southern North Sea - Wöhlbrand, Lars; Wemheuer, Bernd; Feenders, Christoph; Ruppersberg, Hanna S.; Hinrichs, Christina; Blasius, Bernd; Daniel, Rolf; Rabus, Ralf (Frontiers in Microbiology, 2017)
Annually recurring phytoplankton spring blooms are characteristic for temperate coastal shelf seas. During such periods environmental factors like nutrient availability are considerably different from non-bloom conditions, affecting the entire ecosystem including the bacterioplankton. Accordingly, the emerging ecological niches during bloom transition are occupied by different bacterial populations, with Roseobacter RCA cluster and SAR92 clade members exhibiting high metabolic activity during bloom events. In this study, the functional response of the ambient bacterial community towards a Phaeocystis globosa bloom in the southern North Sea was studied using metaproteomic approaches. Different to other metaproteomic studies of marine bacterial communities, this is the first study comparing two different cell lysis and protein preparation methods (using trifluoroethanol (TFE) and in-solution digest as well as bead beating and SDS-based solubilization and in-gel digest (BB GeLC)). In addition, two different mass spectrometric techniques (ESI-iontrap MS and MALDI-TOF MS) were used for peptide analysis. A total of 585 different proteins have been identified, 296 of which were only detected using the TFE and 191 by the BB GeLC method, demonstrating the complementarity of these sample preparation methods. Furthermore, 158 proteins of the TFE cell lysis samples were exclusively detected by ESI-iontrap MS while 105 were only detected using MALDI-TOF MS, underpinning the value of using two different ionization and mass analysis methods. Notably, 12% of the detected proteins represent predicted integral membrane proteins, including the difficult to detect rhodopsin, indicating a considerable coverage of membrane proteins by this approach. The comprehensive approach verified previous metaproteomic studies of marine bacterioplankton, e.g. detection of many transport-related proteins (17% of the detected proteins). In addition, new insights into e.g. carbon and nitrogen metabolism were obtained. Apparently, the C1 pathway is more prominent outside the bloom and different strategies for glucose metabolism seem to be applied under the studied conditions. Furthermore, a higher number of nitrogen assimilating proteins were present under non-bloom conditions, reflecting the competition for this limited macro nutrient under oligotrophic conditions. Overall, application of different sample preparation techniques as well as MS methods facilitated a more holistic picture of the marine bacterioplankton response to changing environmental conditions.